Do Type of Insurance, Geographical Variation and Type of Practice Impact Access to Foot and Ankle Care?. Issue 4 (16th October 2019) - Jain, Mohit; McKissack, Haley; He, Jun Kit; Jha, Aaradhana J.; Anderson, Matthew; Pitts, Charles; Brahmbhatt, Ashish; Momaya, Amit
Category: Foot & Ankle Introduction/Purpose: Medical coverage gap in United States refers to people who are uninsured because the state they are living has still opted-out of Medicaid expansion under Patient Protection and Affordable Care Act (PPACA) and they are too poor to be benefited from subsidies designed for middle-class Americans. A large percentage of this population lives in south. Despite increasing participation of the states in expanded Medicaid, it is still unclear that if such an expansion has led to improve the access to care. However, approximately one in three American is covered under Blue Cross Blue Shield (BCBS) private insurance. The purpose of this study is to determine the access to foot and ankle care based on medical insurance, nature of illness and Medicaid expansion of the state. Methods: Five pairs of Medicaid expended (California, New York, Ohio, Minnesota and Washington) and non-expanded (Utah, Texas, Alabama, Missouri, and North Carolina) states with different geographic location were selected for the study. Twenty providers from each state were randomly selected via American Orthopedic Foot & Ankle Society (AOFAS) directory with private or academic affiliations. Each provider's office was contacted by fictitious call for the earliest available appointment in foot and ankle clinic. A standardized script was used by the same researcher every time for a 30 year old male patient with acute Achilles tendon rupture or chronic bunion with either Medicaid or BCBS insurances. Available appointment for physician was considered as an access to foot and ankle care. We registered time until appointment (if given) and reason for denial (if denied) on phone. We also recorded requirements for insurance details, PCP (Primary Care Physician) referral or imaging records. Results: 200 providers' offices were contacted on phone for foot and ankle clinic appointment. Successful appointment was given by 36%(72/200) offices irrespective of condition and insurance. 29% of calls with Medicaid could successfully schedule an appointment compared to 43% when calling with BCBS(P=0.03). Success rate for appointment was same for Achilles rupture and Bunion (36% each). The mean time until earliest appointment was 10.7(range 1-37) days with Medicaid and 10.5 (range 1-45) days with BCBS. For Medicaid patients, no significant difference was found in appointment rates between expanded states (30%) and non-expanded (28%) states (P=0.82). Overall appointment success rate was highest in Utah (65%) and lowest in New York (10%). Differences were observed across geographical locations, as well as between academic and private institutes. Conclusion: In our study, access to foot and ankle care clinic seems to be significantly better with BCBS private insurance compared to Medicaid. Sample size is surely a limitation, but we have included more states than similarly-designed studies for better geographic variability. There was no significant difference for appointment wait-time between Achilles tendon rupture and Bunion as well as Medicaid and BCBS insurance. Medicaid expansion facility in the state has not been associated with higher success rate but associated with lengthening of wait-time. Inability to provide insurance details or PCP-referral is definitely an important barrier for the access to podiatric care.